2022
DOI: 10.1002/rob.22071
|View full text |Cite
|
Sign up to set email alerts
|

Lifting‐principle‐based design and implementation of fixed‐wing unmanned aerial–underwater vehicle

Abstract: This paper presents the implementation of a novel proof‐of‐concept design of a fixed‐wing unmanned aerial–underwater vehicle (UAUV). The UAUV is designed on the basis of the lifting principle and has an overall density between those of water and air. During air flight, fixed‐wings are deployed to create lift to overcome gravity, similar to ordinary fixed‐wing aircraft. Moreover, the fixed‐wings generate sufficient downward lift to overcome the large net buoyancy (FB), allowing the vehicle to dive during underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…The results of underwater propulsion tests conducted by Wei et al for air propellers showed that the propulsion efficiency of air propellers operating underwater was lower than that in air, and the tests in this paper yielded different results as shown in Figure 14 (Z. Wei, Teng, et al, 2022). This may be due to the different motor‐propeller matching.…”
Section: System Overview Of the Foldable Wing Uauvmentioning
confidence: 68%
See 2 more Smart Citations
“…The results of underwater propulsion tests conducted by Wei et al for air propellers showed that the propulsion efficiency of air propellers operating underwater was lower than that in air, and the tests in this paper yielded different results as shown in Figure 14 (Z. Wei, Teng, et al, 2022). This may be due to the different motor‐propeller matching.…”
Section: System Overview Of the Foldable Wing Uauvmentioning
confidence: 68%
“…The air propellers on the left and right sides of this vehicle are used for air and underwater propulsion, and it can be submerged from the surface by means of elevator. The paper presents the relevant experiments and summarizes the motion characteristics of this type of dual‐propulsion vehicle (Z. Wei, Teng, et al, 2022). Rockenbauer et al developed a 3.1 kg lightweight foldable wing UAUV and designed a dual‐use air–water propulsion system to achieve trans‐medium access in the simplest possible design and manufacturing form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These qualities allow them to accomplish tasks independently, avoiding traditional multivehicle collaboration. [9,10] Besides, aerial-aquatic robots are able to traverse complex multiphase environments, which makes them suitable for a wide range of applications, [10][11][12][13][14] such as disaster rescue, environmental exploration, ecosystem monitoring, and reservoir management.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two years, and concurrent with our LOSSEI research, there has been a spate of Chinese publications documenting the design and testing of HUAVs, starting with the design fabrication and characterisation of a HUAV in 2021 [11], followed by 2022 research into lifting principles [12], a numerical simulation of air-water transition [13], further design, fabrication, and experimentation [14], cross-domain control [15], and a miniature low-cost HUAV [16]. Such work confirms that some technologies have progressed for HUAVs sufficiently for us to recommend substantive proof-of-concept testing for this and other such hybrid vehicles.…”
Section: Introductionmentioning
confidence: 99%